1957
DOI: 10.2307/1538873
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Polysaccharides and Basophilic Substances During the Development of the Mushroom Coprinus

Abstract: As Buller (1909 ct scq.) has pointed out, some species of the genus Copriniis sow their spores once during a short interval of time and the fruiting body disappears shortly thereafter by auto-digestion. Characteristically the small buds will, all in one clay, go through a period of rapid expansion and elongation, shed their spores, and deliquesce. This rapidity is no doubt related to their small size, for larger species of hymenomycetes will go through many days of continued production and shedding of spores.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1958
1958
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, inhibition studies with ammonium and analysis of white cap mutants indicated that glycogen degradation and sporulation are not closely coupled (188,345). Glycogen synthetase activity is low during spore production but increases during basidiospore maturation (188), obviously to produce the glycogen that is found in the mature spores (37,169,312).…”
Section: Physiological Factorsmentioning
confidence: 99%
“…However, inhibition studies with ammonium and analysis of white cap mutants indicated that glycogen degradation and sporulation are not closely coupled (188,345). Glycogen synthetase activity is low during spore production but increases during basidiospore maturation (188), obviously to produce the glycogen that is found in the mature spores (37,169,312).…”
Section: Physiological Factorsmentioning
confidence: 99%
“…These glycogen accumulations remain at the base of the stipe of the developing fruit body (Matthews & Niederpruem, 1973). At later stages, glycogen becomes concentrated in distinct zones in the hymenium of the gills of expanding fruits and is translocated into the spores when sporulation occurs (Bonner et al, 1957). In the vegetative mycelium, glycogen is involved in the maturation of small perennating bodies called sclerotia (Waters, Moore & Butler, 1975 b).…”
Section: Introductionmentioning
confidence: 99%